Metabolic Dysfunction-Associated Steatotic Liver Disease Is Accompanied by Increased Activities of Superoxide Dismutase, Catalase, and Carbonyl Reductase 1 and Levels of miR-200b-3p in Mouse Models - Gabriela Svobodová; Michaela Šadibolová; Eva Velecká; Lucia Mráziková; Petra Vaculová; Petra Matoušková; Jaroslav Kuneš; Lenka Maletínská; Iva Boušová (MDPI AG, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD), one of the leading causes of chronic liver disorders, is characterized by hepatic lipid accumulation. MASLD causes alterations in the antioxidant defense system, lipid, and drug metabolism, resulting in impaired antioxidant status, hepatic metabolic processes, and clearance of therapeutic drugs, respectively. In the MASLD pathogenesis, dysregulated epigenetic mechanisms (e.g., histone modifications, DNA methylation, microRNAs) play a substantial role. In this study, the development of MASLD was investigated in mice fed a high-fat, high-fructose, and high-cholesterol (FFC) diet from 2 months of age, mice treated neonatally with monosodium glutamate (MSG) on a standard diet (STD), and mice treated with MSG on an FFC diet at 7 months of age and compared to control mice (C) on STD. Changes in liver histology, detoxification enzymes, epigenetic regulation, and genes involved in lipid metabolism were characterized and compared. The strong liver steatosis was observed in MSG STD, C FFC, and MSG FFC, with significant fibrosis in the latter one. Moreover, substantial alterations in hepatic lipid metabolism, epigenetic regulatory factors, and expressions and activities of various detoxification enzymes (namely superoxide dismutase, catalase, and carbonyl reductase 1) were observed in MASLD mice compared to control mice. miR-200b-3p, highly significantly upregulated in both FFC groups, could be considered as a potential diagnostic marker of MASLD. The MSG mice fed FFC seem to be a suitable model of MASLD characterized by both liver steatosis and fibrosis and substantial metabolic dysregulation.